Predictors of seasonal influenza and COVID-19 vaccination coverage among adults in Tennessee during the COVID-19 pandemic - J. Cunningham-Erves; W. George; M. Sanderson; E. Stewart; S. W. Jin; J. Davis; H. M. Brandt (Frontiers Media S.A., 2024)
BackgroundThe COVID-19 pandemic has convoluted hesitancy toward vaccines, including the seasonal influenza (flu) vaccine. Because of COVID-19, the flu season has become more complicated; therefore, it is important to understand all the factors influencing the uptake of these vaccines to inform intervention targets. This article assesses factors related to the uptake of influenza and COVID-19 vaccines among adults in Tennessee.MethodsA cross-sectional, secondary data analysis of 1,400 adults was conducted in Tennessee. The adult sample came from two data sources: Data source 1 completed a baseline survey from January to March 2022, and data source 2 was completed from May to August 2022. Data on vaccine attitudes, facilitators and barriers, and communication needs were collected via random digit dial by Scientific Telephone Samples (STS). Two multivariable logistic regression models were used to estimate adjusted odds ratios (aORs) and 95% confidence intervals (CIs) to predict sociodemographic and overall vaccine-related factors associated with receipt or non-receipt (referent) of COVID-19 and influenza vaccines.ResultsApproximately 78% of the adult sample had received the COVID-19 vaccination. A significant positive association for COVID-19 vaccine uptake was seen among those who were older (aged 50-65) (aOR = 1.9; 95% CI: 1.2-3.2), Black (aOR = 2.0; 95% CI:1.3-2.8), and had a college education and higher (aOR = 2.3; 95% CI: 1.5-3.6). However, there was a significant negative association for persons reporting they were extremely religious (aOR = 0.5; 95% CI:0.3-0.9). Over 56% of the adult sample had received the influenza vaccination this season. Those who had a higher annual household income ($80,000+) (aOR = 1.9; 95% CI: 1.3-2.6) and had health insurance (aOR = 2.6; 95% CI: 1.4-4.8) had a significant positive association with influenza vaccine receipt. However, those who were employed part-time or were unemployed had a significant negative association for influenza vaccine receipt (aOR = 0.7; 95% CI: 0.5-0.9). Both COVID-19 and influenza vaccine receipt had strongly significant positive trends with increasing belief in effectiveness and trust (p < 0.0001) and strongly significant negative trends with higher levels of overall vaccine hesitancy (p < 0.0001).ConclusionStrategies to increase COVID-19 and influenza vaccination should be age-specific, focus on increasing geographical and financial access, and offer tailored messages to address concerns about these vaccines.